Subclinical hypothyroidism and associated cardiovascular risk factor in perimenopausal females - Gitanjali Goyal; Lajya Devi Goyal; Heena Singla; Sheenam; Kirti Arora; Harsharan Kaur (Wolters Kluwer Medknow Publications, 2020)
Background: Perimenopause refers to the period around menopause (40-55 years). This includes the period before menopause and the first year after menopause. Perimenopausal age is an important stage in a women's life. Many women are diagnosed with hypothyroidism at midlife. Hypothyroidism - both overt and subclinical are associated with increased risk of CVS diseases. Subclinical hypothyroidism is more important as this stage is usually ignored from treatment point of view and if early intervention is done in SCH worsening of metabolic derangement may be avoided. Objectives: The present study was aimed to know the prevalence of subclinical hypothyroidism and associated dyslipidemia in perimenopausal females. Material and Methods: In our retrospective study we took 100 perimenopausal females (40-55years) who were investigated for thyroid and lipid profile. Atherogenic indices like TC/HDL-c, LDL-c/HDL-c, TG/HDL-c ratios were calculated from the individual lipid profile parameters. The reference guidelines for lipid profile was according to NCEP ATP III. Result: Subclinical hypothyroidism was found to be present in 18% of perimenopausal females The mean TSH levels were found to be higher in SCH as compared to euthyroid females with a mean value of 7.56±3.54(μIU/ml). Dyslipidemia was seen in patients with SCH. TSH levels were found to be positively correlated with total cholesterol. Conclusion: We conclude that subclinical hypothyroidism is present in 18% females of perimenopausal age group. Increased TSH levels are associated with hypertension, hypertriglyceridemia, and elevated TC/HDL-C ratio and non cholesterol HDL. In perimenopausal women the condition is usually underdiagnosed and ignored but subclinical hypothyroidism in these females should be screened and treated timely to decrease the risk of accelerated atherosclerosis and premature coronary artery disease in them.